PERAN UNITED NATIONS WOMEN DALAM MENANGGULANGI DISKRIMINASI TERHADAP PEREMPUAN DI AFGHANISTAN - Fitrah Awaliyah Rumadaul (Global Political Studies Journal, 2017)
The study aims to describe how the role of the UN Women in overcoming women's discrimination in Afghanistan. The researcher also intends to find out what steps are taken by UN Women in tackling discrimination against women in Afghanistan, and want to find out what are the obstacles faced by the UN Women when tackling discrimination in women in Afghanistan, and how the organization's success in combating discrimination against women in Afghanistan in 2014-2016. The research method used by the author in this study is a qualitative method. Most of the data is collected through library studies, online data searches and documents. The research was conducted by the Indonesian Institute of Sciences (LIPI). The theories used by researchers are the theory of international relations, international organizations, the role of international organizations, human rights, women's rights and gender in international relations. The results of this study indicate that the role of UN Women in tackling discrimination against women in Afghanistan can not be separated from various kinds of obstacles. However, the programs carried out by UN Women still have a considerable impact, especially in increasing awareness regarding the importance of the role of women in a country. The conclusions show that there were changes when the UN Women entered the Afghan region, it was seen how UN Women was able to overcome discrimination in various ways that the UN Women did, and these changes brought positive damages for women in Afghanistan.